Anemia of Inflammation & Health-Related Quality of Life in Chronic Kidney Disease - Ghosh, Liton Chandra; Akhter, Mahbuba; Saha, Swapon Kumer; Sarker, Nayan Ranjan (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Anemia is a common comorbidity of chronic kidney disease (CKD). As the diseased kidney loses its ability to produce the erythropoietin essential to the production of hemoglobin, anemia ensues. Anemia is observed in the course of chronic kidney disease (CKD) and it is associated with diminishing the quality of a patient's life. Moreover, it enhances morbidity and mortality and hastens the CKD progression rate. Objective: To analyze the health-related quality of life (HRQOL) in anemic CKD patients with the effects of anemia and inflammation Methods: This cross-sectional study was conducted in the Department of Nephrology, (Dhaka national medical college and hospital), Dhaka, for 2 years; from January 2018 to December 2019. A total of 50 subjects fulfilling the inclusion criteria were enrolled as study subjects.Data were processed and analyzed using the software SPSS (Statistical Package for Social Sciences) version 11.5 Result: Among the study subjects, most patients (30, 60.0%) belonged to the age group of> 55 years, followed by 15 (30.0%) patients were from 50-55 years of age and the rest 5 (10.0%) patients were from 45-50 years of age. About 60% of the patients were male and 40% were female in this study. Concerning the degree of anemia, most of the patients (25, 50.0%) suffered from severe anemia followed by 17 (34.0%) patients had moderate anemia, and the rest 8 (16.0%) patients had mild anemia. According to extent of CKD, most of the patients (25,50.0%) had stage 5 CKD (ESRD), followed by 15 (30.0%) patients had stage 3 CKD, and the rest 10 (20.0%) patients suffered from stage 4 kidney disease. Among the patients who had stage 3 kidney disease, 8 (16.0%) patients had mild anemia, followed by 4 (8.0%) patients had moderate anemia, and the rest 3 (6.0%) patients had severe anemia. Among the patients with stage 4 CKD, 6 (12.0%) patients had moderate anemia and 4 (8.0%) patients had severe anemia. Among the patients who had the end-stage renal disease (ESRD) or stage 5 CKD, 7 (14.0%) patients had moderate anemia and 18 (36.0%) patients had severe anemia. Considering inflammatory parameters according to the degree of anemia, the neutrophil count was >6000 U/L, 6000-6500 U/L, and 6500-7500 U/L in mild, moderate, and severe anemia respectively. Lymphocyte count was <5000 U/L, 5000-5400 U/L, and 5000-5500 U/L in mild, moderate, and severe anemia respectively. CRP (mg/dl) level was 0.9- 2 in mild anemia, 5-40 in moderate anemia, and 10-50 in severe anemia. Conclusion: This study highlighted the profound impact of CKD on health-related quality of life (HRQOL) and potential areas that can be targeted for therapeutic intervention. Furthermore, this study showed, chronic diseases can lead to an inflammatory process which ultimately results in anemia through various mechanisms. Moreover, early identification and correction of anemia may improve the quality of life. J. Dhaka National Med. Coll. Hos. 2023; 29 (01): 25-29